Risk and Protective Factors in Choosing Course Sets in Secondary Education: Perspectives of Career Counsellors and Students from the Latgale Region of Latvia - Pancerko, Pāvels; Pipere, Anita; Kravale-Pauliņa, Mārīte (Acta Paedagogica Vilnensia, 2022)
This paper presents an exploratory study of the perspectives of career counsellors and students on risk and protective factors in choosing course sets in secondary education. The study, conducted in the Latgale region of Latvia, uses a qualitative research design based on a triangulation between the perspectives of school career counsellors and students. Data obtained from interviews with four career counselors and a focus group with six 15–16 year old students from urban and rural schools were analyzed using thematic analysis. The study acknowledges that school career counsellors can serve as a vital resource for Latvian society in managing and addressing the challenges of current educational reform and inequalities in education and career management caused by socioeconomic disparities.